Quitting Failure and Success With and Without Using Medication: Latent Classes of Abstinence and Adherence to Nicotine Monotherapy, Combination Therapy, and Varenicline. Issue 11 (9th August 2018) - McCarthy, Danielle E; Versella, Mark V
Abstract: Introduction: Nonadherence to pharmacotherapies complicates studies of comparative pharmacotherapy effectiveness. Modeling adherence and abstinence simultaneously may facilitate analysis of both treatment acceptability and effectiveness. Methods: Secondary analyses of a three-arm randomized comparative trial of nicotine patch, varenicline, and combination nicotine patch and lozenge among adult daily smokers ( N = 1086) were conducted. Adherence rates collected via interactive voice response systems during the first 27 days of quitting were compared across treatment conditions. Repeated measures latent class analyses of adherence and abstinence in 3-day parcels through 27 days of a quit attempt were conducted with treatment, demographic, and smoking history covariates. Results: Adherence varied across treatments and was lowest for nicotine lozenge use in combination nicotine replacement therapy (NRT). Five latent classes that differed significantly in 6-month abstinence rates were retained, including three subgroups of adherent participants varying in treatment response and two nonadherent groups varying in abstinence probabilities. Nonadherence was more likely among those receiving varenicline and combination NRT, relative to patch monotherapy. Varenicline and combination NRT did not promote abstinence among adherent latent classes but did promote abstinence among those partially adherent, relative to patch alone. Combination therapy attenuated increased risk of treatment disengagement with more years smoking. Minority smokers, those high in dependence, and those with shorter past abstinence were at increased risk for low-adherence and low-abstinence latent classes. Conclusions: Varenicline and combination nicotine patch and lozenge are less likely to be used as directed and may not increase first-month abstinence better than patch alone when taken adherently. Implications: This secondary analysis of adherence and abstinence in a comparative effectiveness trial shows that adherence is highest for the nicotine patch, next highest for varenicline, and lowest for combination nicotine patch and lozenge therapy due to low lozenge use. Distinct latent classes were found that varied in both first-month abstinence and adherence. Varenicline and combination NRT may not enhance abstinence over patch alone among smokers who take medication adherently. Adherent use of medication especially benefits those who are low in dependence and have positive quitting histories; it is less beneficial to at-risk smokers and members of racial minorities.